VACUUM ASSISTED CLOSURE OF LAPAROSTOMY WOUNDS A NOVEL TECHNIQUE - Andrabi, Syed Imran Hussain; Ahmad, Jawad; Rathore, Munir A; Yousaf, Muhammad (Journal of Ayub Medical College Abbottabad, 2007)
Management of a laparostomy wound is contentious. Specific pathologies like severe intraabdominal sepsis, trauma requiring damage control, abdominal compartment syndrome, staged abdominal repair and other complex abdominal pathologies can be managed with a novel technique of Vacuum Assisted Closure dressing. This device applies sub-atmospheric pressure that leads to reduced bowel wall edema , bacterial count and inflammatory burden found in open abdominal wounds. This leads to a reduced need for frequent dressing changes, maintaining intact skin and improvement in fluid management. Controlled clinical studies are needed to establish the safety and effectiveness of this treatment strategy. We present our experience with this technique suggesting it to be safe and effective. A brief outline of the working of Vacuum Assisted Closure dressing is also presented. Keywords: Vacuum assisted closure, dressing, laparostomy, burst abdomen, open abdomen